Acceptance and Decision Making in Amyotrophic Lateral Sclerosis From a Life-Course Perspective. (January 2014) - Foley, Geraldine; Timonen, Virpi; Hardiman, Orla
Researchers have explored perceptions of health care services among people with amyotrophic lateral sclerosis (ALS), but little is known about how and why people with ALS engage with services. We undertook a grounded theory study to identify key psychosocial processes that underpin how and why people with ALS engage with health care services. We conducted in-depth interviews with 34 participants sampled from the Irish ALS population-based register. We found that age and life stage shaped participants' decision making about care. Participants in later life were more accepting of ALS and of death than young and middle-aged participants. Family was the primary context to how participants engaged with services, and their decisions about care were shaped by parenthood at different life stages. Health care professionals need to be attuned to the impact of life-course trajectories and family relations on the decisions people with ALS make about their care.